Effect of Cu2+ on Corrosion Behavior of A106B Carbon Steel and 304L Stainless Steels in Seawater. (6th October 2021) - Fang, Kewei; Li, Chengtao; Dong, Shuai; Zhang, Dubao; Wu, Xiangfeng; Hu, Hongxiang
Abstract : The corrosion behaviors of A106B carbon steel and 304L stainless steel (SS) in seawater with different Cu 2+ concentrations were studied by the immersion test and the potentiodynamic polarization test. The results showed that with the increasing Cu 2+ concentration, the mass lot rates of A106B and 304L SS all increased in the immersion test, and compared with A106B, the mass lot rates of 304L SS were all smaller. In the potentiodynamic polarization test, following the concentration of Cu 2+ increased, the corrosion potential of A106B firstly shifted negatively; then, when Cu 2+ increased to 100 ppm, the polarization curve moved to the upper right direction; namely, both the corrosion potential and corrosion electrical density increased. The corrosion potential of 304L SS increased with the increasing Cu 2+, and the passive region was reduced; the pitting sensitivity improved.